High-performance ASIC design : using synthesizable domino logic in an ASIC flow - Hossain, Razak, 1965- (Cambridge University Press, 2008)
Presenting a methodology for using domino logic in an ASIC design flow developed over several years in an industrial context, this text covers practical issues related to the use of domino logic in an automated framework, and brings together all the knowledge needed to apply these design techniques in practice. Beginning with a discussion of how to achieve high speed in ASIC designs, subsequent chapters detail the design and characterization of standard cell compatible domino logic libraries and an advanced domino logic synthesis flow. The results achieved by using automated domino logic design techniques, including silicon measurements, are used to validate the presented solution. With design examples including the implementation of the execution unit of a microprocessor and a Viterbi decoder, this text is ideal for graduate students and researchers in electrical and computer engineering and also for circuit designers in industry.